Diagnostic potential of plasma biomarkers and exhaled volatile organic compounds in predicting the different stages of acute mesenteric ischaemia: protocol for a multicentre prospective observational study (TACTIC study) - Marco J Bruno; Kaatje Lenaerts; Eline S van Hattum; Jaap F Hamming; Olaf J Bakker; Ron Balm; Maarten J van der Laan; Gert Jan de Borst; Mathias Clarysse; Laurens J Ceulemans; Adriaan Moelker; Dammis Vroegindeweij; et al. (BMJ Open)
Introduction Acute mesenteric ischaemia (AMI) is a life-threatening condition with short-term mortality of up to 80%. The diagnosis of AMI has remained troublesome due to the non-specific clinical presentation, symptoms and laboratory findings. Early unambiguous diagnosis of AMI is critical to prevent progression from reversible to irreversible transmural intestinal damage, thereby decreasing morbidity and improving survival. The present study aims to validate a panel of plasma biomarkers and investigate volatile organic compound (VOC) profiles in exhaled air as a tool to timely and accurately diagnose AMI.Methods and analysis In this international multicentre prospective observational study, 120 patients (>18 years of age) will be recruited with clinical suspicion of AMI. Clinical suspicion is based on: (1) clinical manifestation, (2) physical examination, (3) laboratory measurements and (4) the physician’s consideration to perform a CT scan. The patient’s characteristics, repetitive blood samples and exhaled air will be prospectively collected. Plasma levels of mucosal damage markers intestinal fatty acid-binding protein and villin-1, as well as transmural damage marker smooth muscle protein 22-alpha, will be assessed by ELISA. Analysis of VOCs in exhaled air will be performed by gas chromatography time-of-flight mass spectrometry. Diagnosis of AMI will be based on CT, endovascular and surgical reports, clinical findings, and (if applicable) verified by histopathological examination.Ethics and dissemination The study protocol was approved by the Medical Research Ethics Committee (METC) of Maastricht University Medical Centre+ and Maastricht University (METC azM/UM), the Netherlands (METC19-010) and the Ethics Committee Research UZ/KU Leuven, Belgium (S63500). Executive boards and local METCs of other Dutch participating centres Gelre Ziekenhuizen (Apeldoorn), Medisch Spectrum Twente (Enschede), and University Medical Centre Groningen have granted permission to carry out this study. Study results will be disseminated via open-access peer-reviewed scientific journals and national/international conferences.Trial registration number NCT05194527.